Chemical Synthesis, Characterization, and Biocompatibility Study of Hydroxyapatite/Chitosan Phosphate Nanocomposite for Bone Tissue Engineering Applications - Nabakumar Pramanik; Debasish Mishra; Indranil Banerjee; Tapas Kumar Maiti; Parag Bhargava; Panchanan Pramanik (International Journal of Biomaterials)
A novel bioanalogue hydroxyapatite (HAp)/chitosan phosphate (CSP) nanocomposite has been synthesized by a solution-based chemical methodology with varying HAp contents from 10 to 60% (w/w). The interfacial bonding interaction between HAp and CSP has been investigated through Fourier transform infrared absorption spectra (FTIR) and x-ray diffraction (XRD). The surface morphology of the composite and the homogeneous dispersion of nanoparticles in the polymer matrix have been investigated through scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. The mechanical properties of the composite are found to be improved significantly with increase in nanoparticle contents. Cytotoxicity test using murine L929 fibroblast confirms that the nanocomposite is cytocompatible. Primary murine osteoblast cell culture study proves that the nanocomposite is osteocompatible and highly in vitro osteogenic. The use of CSP promotes the homogeneous distribution of particles in the polymer matrix through its pendant phosphate groups along with particle-polymer interfacial interactions. The prepared HAp/CSP nanocomposite with uniform microstructure may be used in bone tissue engineering applications.